Single- and Double-Layer Microwave Absorbers of Cobalt Ferrite and Graphite Composite at Gigahertz Frequency - Ismail I.; Matori K.A.; Abbas Z.; Zulkimi M.M.M.; Idris F.M.; Zaid M.H.M.; Rahim N.; Hasan I.H.; Song W.H. (Springer New York LLC, 2023)
Activation energy; Arrhenius plots; Cobalt; Cobalt alloys; Cobalt compounds; Crystallography; Electromagnetic waves; Ferrite; Graphite; Hematite; Iron alloys; Particle size; Sintering; Cobalt ferrites; Double layer structure; Microwave absorbers; Reflection loss; Single layer; Mixer circuits